1995
DOI: 10.1016/0896-6273(95)90245-7
|View full text |Cite
|
Sign up to set email alerts
|

Immediate differentiation of ganglion cells following mitosis in the developing retina

Abstract: The aim of this study is to gain insight into the time during the life history of a retinal neuron that it becomes committed to a particular phenotype. At this point, it is not possible to identify the time of commitment, but the time that differentiation begins can be identified. Bromodeoxyuridine labeling coupled with immunohistochemistry with a ganglion cell-specific antibody was used to fix the time of the beginning of ganglion cell differentiation relative to the time of mitosis in the developing chick re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 41 publications
8
89
0
Order By: Relevance
“…We present three independent sets of experiments demonstrating that Notch1 transcription is regulated by SOX2; an unbiased ChIP screen identified Notch1 as a direct target of SOX2 in vivo, DNase footprinting and Luciferase reporter assays showed that SOX2 can bind to Notch1 regulatory regions and regulate the levels of NOTCH1 expression in vitro, and finally, both NOTCH1 and its target Hes-5 are dramatically down-regulated in the retinas of Sox2 hypomorphic mice. Furthermore, ablation of NOTCH1 gives a retinal phenotype similar to that which we describe for Sox2-null mice (i.e., loss of RPCs) (Austin et al 1995;Waid and McLoon 1995;Ahmad et al 1997;Henrique et al 1997;Jadhav et al 2006), and the retinal phenotypes of both Hes-1 and Hes-5 mutant mice are strikingly similar to the phenotype observed in Sox2-hypomorphic mice, in that RPCs aberrantly differentiate and abnormal "rosette-like" structures are present (Ishibashi et al 1994;Tomita et al 1996). The lack of balance between lateral inhibitory signaling by NOTCH1 and proneural gene products results in differentiation of RPCs-a mechanism that may extend to other CNS progenitors.…”
Section: Sox2 and Retinal Progenitor Fate Genes And Development 1197mentioning
confidence: 78%
“…We present three independent sets of experiments demonstrating that Notch1 transcription is regulated by SOX2; an unbiased ChIP screen identified Notch1 as a direct target of SOX2 in vivo, DNase footprinting and Luciferase reporter assays showed that SOX2 can bind to Notch1 regulatory regions and regulate the levels of NOTCH1 expression in vitro, and finally, both NOTCH1 and its target Hes-5 are dramatically down-regulated in the retinas of Sox2 hypomorphic mice. Furthermore, ablation of NOTCH1 gives a retinal phenotype similar to that which we describe for Sox2-null mice (i.e., loss of RPCs) (Austin et al 1995;Waid and McLoon 1995;Ahmad et al 1997;Henrique et al 1997;Jadhav et al 2006), and the retinal phenotypes of both Hes-1 and Hes-5 mutant mice are strikingly similar to the phenotype observed in Sox2-hypomorphic mice, in that RPCs aberrantly differentiate and abnormal "rosette-like" structures are present (Ishibashi et al 1994;Tomita et al 1996). The lack of balance between lateral inhibitory signaling by NOTCH1 and proneural gene products results in differentiation of RPCs-a mechanism that may extend to other CNS progenitors.…”
Section: Sox2 and Retinal Progenitor Fate Genes And Development 1197mentioning
confidence: 78%
“…It is widely accepted that there are axons from ganglion cells in NFL, dendrites from ganglion cells, neurites from amacrine cells, and axons from bipolar cells in IPL, and dendrites from bipolar cells, neurites from horizontal cells, and rod spherules and cone pedicles in OPL. Differentiation of ganglion cells for neuronal outgrowth in developing chicken retina has been shown, by using a ganglion cell-specific antibody (Waid and McLoon, 1995), to begin on E3 and continue to E9, with the peak on ES.…”
Section: Discussionmentioning
confidence: 99%
“…Since RA4 labels retinal ganglion cells (Waid & McLoon, 1995) that also express HNK-1/N-CAM (Andressen et al, 1999; our own observation), MAP2 (Tucker & Matus, 1987), and Islet-1 (Austin et al, 1995), we examined whether these markers were expressed in RPE cell cultures treated with bFGF. Monoclonal antibody against Islet-1 stained the nuclei of ganglion cells in the retina (Austin et al, 1995; our own observation) but did not yield immuno-staining signals when applied to the RPE cultures.…”
Section: Bfgf Induced the Expression Of Ra4 Immunogenicitymentioning
confidence: 95%
“…Immunocytochemical staining with monoclonal antibody RA4, which in the retina labels ganglion cells (Waid & McLoon, 1995), detected thousands of positive cells in E6 RPE cultures treated with 25 mg/ml of bFGF ( Fig. 2; Table 1).…”
Section: Bfgf Induced the Expression Of Ra4 Immunogenicitymentioning
confidence: 99%